UPAYA MENINGKATKAN KETERAMPILAN KOLABORASI SISWA MELALUI MODEL PEMBELAJARAN TIPE GROUP INVESTIGATION (GI) PADA MATA PELAJARAN IPAS DI KELAS IV MI NURUL IMAN NWDI PAGUTAN KAB.LOMBOK TENGAH TAHUN PELAJARAN 2025/2026 - Aini, Niswatun; Taufik, Amalia; Hamzan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low collaborative skills of students as indicated by the lack of active participation in group activities, low responsibility in completing joint tasks, and the suboptimal attitude of mutual respect between students. The purpose of this study is to improve the collaborative skills of fourth grade students of MI Nurul Iman NWDI Pagutan through the application of the Group Investigation learning model in the subject of science. This type of research is Classroom Action Research (CAR). The subjects of this study were 36 fourth grade students, while the object of this research is the improvement of students' collaborative skills through the application of the Group Investigation learning model. This research was conducted in two cycles, each consisting of four stages, namely planning, action implementation, observation, and reflection. Data collection techniques used include observation, questionnaires, and documentation. The results of the study indicate that the application of the Group Investigation learning model can improve students' collaborative skills. This can be seen from the average percentage of students' collaborative skills in cycle I of 64.47%, then after improvements in cycle II increased to 87%. The increase from cycle I to cycle II was 22.53%. This improvement occurred across all indicators of collaboration skills, namely actively contributing, working productively, individual and group responsibility, flexibility and compromise, and mutual respect. Based on these research results, it can be concluded that the Group Investigation learning model is effective in improving fourth-grade students' collaboration skills in science.